Bovine Coronavirus and the Associated Diseases - Vlasova, Anastasia N.; Saif, Linda J. (Frontiers in Veterinary Science, 2021)
Coronaviruses (CoVs) possess the largest and most complex RNA genome (up to 32kb) that encodes for 16 non-structural proteins regulating RNA synthesis and modification. Coronaviruses are known to infect a wide range of mammalian and avian species causing remarkably diverse disease syndromes. Variable tissue tropism and the ability to easily cross interspecies barriers are the well-known characteristics of certain CoVs. The 21st century epidemics of severe acute respiratory CoV (SARS-CoV), Middle East respiratory CoV and the ongoing SARS-CoV-2 pandemic further highlight these characteristics and emphasize the relevance of CoVs to the global public health. Bovine CoVs (BCoVs) are betacoronaviruses associated with neonatal calf diarrhea, and with winter dysentery and shipping fever in older cattle. Of interest, no distinct genetic or antigenic markers have been identified in BCoVs associated with these distinct clinical syndromes. In contrast, like other CoVs, BCoVs exist as quasispecies. Besides cattle, BCoVs and bovine-like CoVs were identified in various domestic and wild ruminant species (water buffalo, sheep, goat, dromedary camel, llama, alpaca, deer, wild cattle, antelopes, giraffes, and wild goats), dogs and humans. Surprisingly, bovine-like CoVs also cannot be reliably distinguished from BCoVs using comparative genomics. Additionally, there are historical examples of zoonotic transmission of BCoVs. This article will discuss BCoV pathogenesis, epidemiology, interspecies transmission, immune responses, vaccines, and diagnostics.